Urban Retrofit and Resilience: the Challenge of Energy Efficiency and Vulnerability - Gargiulo, Carmela; Lombardi, Chiara (TeMA - Journal of Land Use, Mobility and Environment, 2016)
Urban retrofit is becoming increasingly established as one of the most effective solutions to contain the energy consumption of the existing building stock, to reduce vulnerability to natural and man-made risk and generally improve the quality of built space. However, the planning of retrofit interventions at urban scale should take account of the actual feasibility of measures lest they remain only on paper. This contribution supplies an overview of the many issues related to the subject of urban regeneration, proposing a procedure to identify practical interventions to minimize costs and maximize benefits, in terms of energy efficiency, an increase in resilience and improvement in the quality of the building stock. This procedure was applied to a case study of a neighborhood in the city of Naples, a high-density urban area which is particularly vulnerable to volcanic and seismic risk, and to risks due to climate change.